Curriculum Management as a Foundation for Effective Schools - Wirtati, Ira; Nasution, Rizki Hasanah; Siregar, Muhammad Fuad Zaini (EDUTEC : Journal of Education And Technology, 2025)
Curriculum management is a vital component of education, encompassing the processes of planning, implementation, evaluation, and continuous development. This study aims to explore various stages of curriculum management, focusing on the curriculum's relevance to student needs, technological advancements, and the challenges faced during its implementation. The research employs a literature review method by analyzing various relevant sources to obtain comprehensive insights into curriculum management. The findings indicate that effective curriculum planning must be based on an analysis of student needs, alignment with labor market demands, and the latest technological developments. In its implementation, teachers play a crucial role as facilitators in integrating innovative learning methods, such as project-based learning and the use of technology. Curriculum evaluation is essential to assess the effectiveness of learning and the relevance of teaching materials. The primary challenges in curriculum management include resistance to change, limited resources, and inadequate use of technology in teaching. Therefore, curriculum innovation, including the adoption of technology and project-based approaches, can enhance learning effectiveness and better prepare students for future challenges. Collaboration among educational institutions, industries, and the community is also pivotal in creating a more relevant and adaptive curriculum.